6, 12-Diphenyl-3, 9-diazatetraasterane-1, 5, 7, 11-tetracarboxylate Inhibits Proliferation, Migration and Promotes Apoptosis in Ovarian Cancer Cells. (3rd September 2020) - Chen, Pingping; Wang, Huibing; Li, Meng; Yang, Linqi; Mou, Feifei; Singh, Bhupinder; He, Jing-Yu; Zhang, Wei
Abstract : 6, 12-Diphenyl-3, 9-diazatetraasterane-1, 5, 7, 11-tetracarboxylate (DDTC) has been synthesized by the photodimerization of 4-phenyl-1, 4-dihydropyridine-3, 5-dicarboxylate. The potential of theercvantitumor activity and mechanism were investigated in vitro using MTT assay in human lung cancer cell line A549, ovarian cancer cell lines SKOV3 and A2780, breast cancer cell line MCF-7, gastric cancer cell line BGC-823, colon cancer cell line HT29, prostate cancer cell line DU145, and liver cancer cell line SMMC7721. The results show that DDTC can inhibit the growth of ovarian cancer SKOV3 and A2780 cells. The best IC50 value is approximately 5.29 ± 0.38 and 4.29 ± 0.39 μ M, respectively. DDTC induced the cell cycle arrest in the G2 phase by flow cytometric analysis. The migration and invasion of ovarian cancer SKOV3 and A2780 cells were inhibited by DDTC. DDTC could increase the expression protein level of E-cadherin in A2780 cells and ascend the expression protein and mRNA levels of E-cadherin in SKOV3 cells. DDTC could also decrease the protein and mRNA expression of EMT (epithelial-to-mesenchymal transition) markers of N-cadherin and Vimentin. mRNA and protein expression level of checkpoint kinase 1 (Chk1) were significantly increased and expressions of cyclin-dependent kinase (CDK1) and cell division cycle 25a (Cdc25a) were decreased in the SKOV3 and A2780 cell lines. Moreover, DDTC induced apoptosis by the cleavage and activation of caspase 3 and caspase 9.